Prematurity and Related Biochemical Outcomes: Study of Bone Mineralization and Renal Function Parameters in Preterm Infants - Sarika Singh Chauhan; Purnima Dey Sarkar; Bhawna Bhimte (Biochemistry Research International)
Preterm is defined as a baby with a gestation of less than 37 completed weeks. In this study, serum calcium, phosphorus, ALP, creatinine, and electrolytes were measured in preterm babies. The present study comprised of 75 preterm babies of which 25 were of 28–30 weeks, 25 were of 30–32 weeks, and remaining 25 were of 34–36 weeks (controls) of gestational age. Serum calcium and phosphorus levels were found to be significantly decreased, and serum ALP, creatinine, and electrolytes were found to be significantly increased (𝑃<0.001) at 28–30 weeks as compared to controls, but serum calcium and phosphorous levels were found to be insignificantly decreased, whereas serum ALP activities were found to be insignificantly increased at 28–30 weeks as compared to 30–32 weeks of gestational age in preterm babies. It can be concluded that high serum ALP activity and low serum calcium and phosphorus levels are associated with preterm babies. A significant difference in the mean values of these renal function parameters was also obtained, except for serum sodium and potassium.